Experimental and numerical investigations on ultra-high toughness cementitious composite slabs subjected to close-in blast loadings. (February 2022) - Xu, Shilang; Chen, Bokun; Li, Qinghua; Zhou, Fei; Yin, Xing; Jiang, Xiao; Wu, Ping
Abstract: This study investigated the dynamic response of one-way square ultra-high toughness cementitious composite (UHTCC) slabs under close-in blast loadings. Six UHTCC slabs and two ordinary concrete slabs with dimensions of 600 mm × 600 mm × 60 mm were subjected to blast loadings at scaled distances of 0.043 m/kg 1/3, 0.085 m/kg 1/3, 0.136 m/kg 1/3, 0.271 m/kg 1/3, 0.407 m/kg 1/3 and 0.356 m/kg 1/3 by varying both charge and distance to the slab. The results indicate the UHTCC displayed better blast resistance performance than the ordinary concrete. Under 200 g TNT blast loadings, the UHTCC slabs presented breaching damage and several cracks and could still bear the load, while the ordinary concrete slabs were broken severely and could not bear load anymore. The existing empirical formulae, including McVays' and UFC 3-340-02, were employed and discussed to predict the failure modes of UHTCC slabs under blast loading. And a formula was proposed to estimate the residual load-carrying capacity of UHTCC slabs and was fitted well with the experimental data. Furthermore, Finite Element (FE) models were developed to study the dynamic response of slabs in LS-DYNA. The findings of this study indicate that the UHTCC has good potential for the constitution of protective structures. Highlights: The dynamic response of UHTCC slabs under blast loading was investigated. The residual load-carrying capacity of slabs after blast loading was tested. Existing empirical prediction methods were discussed to predict the response of slabs. The blast behavior of UHTCC slabs was simulated using the FE model in LS-DYNA.